Non-profit Sector in Pakistan: Government Policy and Future Issues (The Pakistan Development Review, 2002)
The non-profit sector remains relatively small and underdeveloped in Pakistan. During the decade of the 1990s, it has demonstrated some nascent growth resulting from a number of favourable factors like the return to democracy, the growing push towards deregulation and privatisation, the process of globalisation and the emergence of international coalitions of civil society and the deterioration in the financial position of governments which has limited the public provision of social services. The objective of this paper is to examine the role played by government policy in fostering this process of growth of the non-profit sector of Pakistan and to review the key issues faced by the sector at this time. Of particular concern are, first, the overall posture of the government towards the non-profit sector, the types of policies in place, and the underlying philosophy or principles that guide policy-making. Second, the forms of support to the non-profit sector by different levels of government. Third, the posture of international organisations and supranational governments towards local non-profit organisations and, forth, the major issues facing the non-profit sector at the present time.